Men’s Perspectives on Vasectomy Methods: A Health Promotion of Using Contraception - kiranantika, Anggaunita; Tristanti P, Sendhi; Desi Ariwinanti, Desi (KnE Social Sciences, 2020)
Population growth in Indonesia often triggers social conflicts. KB Programmes offer a way to deal with some of the issues arising from a rapidly expanding population, targeting young families. The KB Programme offers advice on health and family planning guidance for men and women. Previously, female contraception was most popular but now males are starting to seek contraception advice (from the local community PLKB counselor). This research considers male participation in and perception of the KB Programmes. Research was conducted based on qualitative methods using area sampling for 15 men in Batu City, East Java Province, Indonesia. Applying the deconstruction theory from Jacques Derrida, this study found that 1) there were still a stereotype that contraception only used mostly for women; 2) counseling from the local counselor helped men to improve their health issues and consider vasectomy as a contraceptive option; 3) men increasingly view vasectomy as a healthy choice and disseminated their views using social media. Keywords: Health Promotion; Vasectomy Methods; Perception; Men’s Acceptors